PENYUSUNAN INDEKS KESADARAN POLITIK DI KALANGAN MAHASISWA - Nabilla Fathasya Arom; Risni Julaeni Yuhan (Politeknik Statistika STIS, 2020)
As agents of change, students are required to have good political awareness. With good political awareness, students have an awareness of their position in a state life order which further strengthens the country's democratic system. So far political awareness has been measured through the level of election participation and Indonesia's democratic index (IDI) specifically aspects of political rights. The measurement is an indirect measurement that sometimes results in different levels of political awareness. Therefore we need a special index to measure one's level of political awareness. Therefore through the study in Polytechnic of Statistics STIS this research aims to describe the variables that affect the level of political awareness of a person and explain the general description of the political awareness level of Polytechnic of Statistics STIS students using the political awareness index (PWI). PWI measurement uses a questionnaire consisting of 36 question covering cognitive, affective, and psychomotor dimentions. Data was collected on June 4th, 2020 with unit of analysis of 140 samples of Polytechnic of Statistics STISstudents taken using the Stratified Circular Systematic Sampling method. The analysis found that political awareness of Polytechnic of Statistics STIS students was in the medium category with each dimention namely cognitive, affective, and psychomotor belong to the category of high, low and high.